2002
DOI: 10.1002/mar.10034
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding the young consumer's brand associations and ethnocentrism in the lion's port

Abstract: This study examines consumer brand associations, focusing on the differences in price perceptions, self-image, and brand -image congruency held for Western and Eastern brands of fashion clothing by young Singaporeans. The study also examines consumer ethnocentric tendencies (CET), finding very low levels of ethnocentrism among respondents, and that ethnocentrism had no effect on brand preference or purchase intention for brands from different origins. ᭧

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 40 publications
5
43
1
1
Order By: Relevance
“…The assumption is consistent with studies conducted in the Republic of Serbia and the countries that have already gone through the transition process . Also, the hypothesis 2 and hypothesis 3 are based on previously conducted research where the factors of consumer ethnocentrism are successfully identified (Acharya and Elliott, 2003;Chryssochoidis, et al, 2007;Miladinović, 2012;O'cass and Lim, 2002;Strehlau, et al, 2012;Upadhya and Singh, 2006). It is expected that the statistical data analysis will isolate the factors from a collected sample of the student population.…”
Section: Short Overview Of Methodology Appliedmentioning
confidence: 99%
“…The assumption is consistent with studies conducted in the Republic of Serbia and the countries that have already gone through the transition process . Also, the hypothesis 2 and hypothesis 3 are based on previously conducted research where the factors of consumer ethnocentrism are successfully identified (Acharya and Elliott, 2003;Chryssochoidis, et al, 2007;Miladinović, 2012;O'cass and Lim, 2002;Strehlau, et al, 2012;Upadhya and Singh, 2006). It is expected that the statistical data analysis will isolate the factors from a collected sample of the student population.…”
Section: Short Overview Of Methodology Appliedmentioning
confidence: 99%
“…Undergraduate students from a major university in China were recruited to participate in the pretest. The targeting of young people for their brand perceptions and evaluations has become both important and challenging for many international firms around the world (O'Cass and Lim 2002). China is no exception, where young people have been described as part of China's millions of "newly rich, fashion-savvy, and globally-minded" consuming generation (as opposed to the "saving generation" of their parents) (Smith and Wylie 2004;Hung et al 2007).…”
Section: Pre-testmentioning
confidence: 97%
“…Studies consistently show that consumer ethnocentrism takes an important role in the consumer's rejection of foreign products (e.g., Kaynak and Kara 2002;Suh and Kwon 2002;Supphellen and Rittenburg 2001;Yu and Albaum 2002). Ethnocentric consumers reject foreign products and accept domestic products so blindly that they cannot identify even the origins of the brands (O'Cass and Lim 2002). They believe that purchasing imports costs domestic jobs, hurts the domestic economy, and is unpatriotic.…”
Section: Consumer Ethnocentrismmentioning
confidence: 99%